Boosting Hydrogen Evolution Reaction Activity of Amorphous Molybdenum Sulfide Under High Currents Via Preferential Electron Filling Induced by Tungsten Doping. Issue 27 (25th July 2022) - Zhang, Dai; Wang, Feilong; Zhao, Wenqi; Cui, Minghui; Fan, Xueliang; Liang, Rongqing; Ou, Qiongrong; Zhang, Shuyu
Abstract: The lack of highly efficient, durable, and cost‐effective electrocatalysts for the hydrogen evolution reaction (HER) working at high current densities poses a significant challenge for the large‐scale implementation of hydrogen production from renewable energy. Herein, amorphous molybdenum tungsten sulfide/nitrogen‐doped reduced graphene oxide nanocomposites (a‐MoWSx /N‐RGO) are synthesized by plasma treatment for use as high‐performance HER catalysts. By adjusting the plasma treatment duration and chemical composition, an optimal a‐MoWSx /N‐RGO catalyst is obtained, which exhibits a low overpotential of 348 mV at a current density of 1000 mA cm −2 and almost no decay after 24 h of working at this current density, outperforming commercial platinum/carbon (Pt/C) and previously reported heteroatom‐doped MoS2 ‐based catalysts. Based on density functional theory (DFT) calculations, it is found that with a reasonable tungsten doping level, the catalytic active site (2S 2 − ) shows excellent catalytic performance working at high current densities because extra electrons preferentially fill at 2S 2 − . The introduction of tungsten tends to lower the electronic structure energy, resulting in a closer‐to‐zero positive Δ G H ∗ $Δ G_{{{\rm{H}}}^{\rm{*}}}$ . Excessive tungsten introduction, however, can lead to structural damage and a worse HER performance under high current densities. The work provides a route towards rationally designing high‐performance catalysts for the HER at industrial‐level currents using earth‐abundant elements. Abstract : This work describes a facile method for synthesizing amorphous molybdenum tungsten sulfide/nitrogen‐doped reduced graphene oxide nanocomposites toward efficient high‐current‐density hydrogen evolution reactions (HER). Density functional theory (DFT) calculations prove that 2S 2 − can be used to maintain high activity with electron injection and the introduction of tungsten tends to induce a closer‐to‐zero positive Δ G H * ${Δ}{G}_{H^{*}}$ under high current densities.